Pelatihan Kewirausahaan untuk Menghasilkan Ide Bisnis Inovatif bagi Siswa SMK - Ida Bagus Ardhi Putra; I Made Dwi Hita Darmawan; Kurniawan Joko Purnomo (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Entrepreneurship is one of the important elements in economic growth in Indonesia when viewed from the number of vocational high school (SMK) graduates who do not get jobs. An Entrepreneurship Seminar was held at SMK Bali Dewata Denpasar with the theme "Entrepreneurship Training to Generate Innovative Business Ideas for Vocational High School Students". The purpose of this seminar was to introduce Accounting students to innovative business ideas based on creativity and technology. The participants were 40 students in grade twelve. These students have studied basic accounting, but they lack creative and innovative thinking in business opportunities. The seminar was conducted with a series of activities including presentations from practitioners, group discussions between students, simulations of business ideas, as well as group presentations by students. This training was very effective because it increased student motivation and understanding of how to develop practical business ideas. Most groups have business ideas that really meet market needs. The results showed that entrepreneurship education with creativity-oriented training can cultivate an entrepreneurial spirit in students so that they are ready to enter the business world or create their own businesses.